Food and feeding habits of the clupeid, Gonialosa manmina (Ham.) from the Kaptai Lake, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Food and feeding habits of Gonialosa manmina were done by the analysis of 197 guts of the fish using both occurrence and point methods and also by the Index of preponderance. As per Index of preponderance, the preferred food items were graded as cladocerans (65.34%-1st), copepods (20.96%-2nd), miscellaneous (8.89%-3rd), rotifers (2.81% 4th) and bacillariophyceae (0.77% 5th). High feeding intensity was observed during pre and post spawning months. Significant (P